Exploring the role of immune biomarkers in idiopathic granulomatous mastitis: A clinical and pathological perspective - Aydin, Umut; Karatas, Ahmet; Artas, Hakan; Artas, Gokhan; Oz, Burak; Aydogdu, Mesude Seda; Koca, Sueleyman Serdar (Elsevier Science Inc, 2025)
Background: Idiopathic granulomatous mastitis (IGM) is a chronic inflammatory disorder characterised by the formation of non-caseating granulomas in breast tissue, primarily affecting young women of childbearing age. The aetiology of IGM remains unclear, with potential factors including trauma, hormonal influences, and autoimmune responses. Recent studies suggest that immune dysregulation may play a critical role in IGM, highlighting the need for exploration of biomarkers involved in inflammation and immune modulation, particularly LL-37, galectin-3, IL-36, and TLR3. Methods: This study included 36 patients diagnosed with IGM and 37 healthy controls. Blood samples were collected from all participants, and serum levels of LL-37, IL-36 alpha, galectin-3, and TLR3 were analyzed using enzyme-linked immunosorbent assay (ELISA). Immunohistochemical evaluations were conducted on breast tissue samples from 16 IGM patients and 10 controls who underwent mammoplasty. Clinical data, including laboratory tests and imaging results, were also collected and analyzed. Statistical analyses were performed using the IBM-SPSS-22.0 software, with significance set at p < 0.05. Results: Serum levels of LL-37, IL-36 alpha, galectin-3, and TLR3 were significantly lower in IGM patients compared to healthy controls (p < 0.001 for all). Immunohistochemical analysis revealed reduced expression of LL-37 in IGM tissue samples, while galectin-3 levels were comparable between the IGM and control groups (p = 0.32). Clinical evaluations indicated significant improvements in inflammatory markers (CRP and ESR) and mass size over the treatment period. Conclusions: The findings of this study suggest that LL-37, IL-36 alpha, galectin-3, and TLR3 are implicated in the pathogenesis of IGM, with their serum levels being significantly diminished in affected patients. The observed reduction in LL-37 may contribute to the decline in IL-36 alpha and TLR3 levels, indicating a potential role of these biomarkers in the inflammatory processes associated with IGM. Further research is warranted to elucidate the mechanisms underlying these alterations and their implications for the diagnosis and treatment of IGM.
Keywords: Anti-citrullinated protein antibody; LL-37; IL-36 alpha; Galectin-3; TLR3; Immune biomarker